2004
DOI: 10.1111/j.1537-2995.2004.04055.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between HBsAg and HBV DNA levels in blood donors who test positive for HBsAg and anti‐HBc: implications for future HBV screening policy

Abstract: HBV DNA levels in HBsAg-positive, anti-HBc-reactive blood donations can be extremely low. About 6 percent of donations would be negative by current minipool HBV NAT methods. About 3 percent of donations would remain undetected by sensitive single-donor NAT. These results indicate caution in any consideration of dropping HBsAg screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 14 publications
5
106
2
1
Order By: Relevance
“…Ozaras et al (2008) suggested that the HBsAg level was correlated with HBV DNA, and that it could replace HBV DNA to monitor the efficacy of pegylated interferon in the presence or absence of lamivudine marker. On the other hand, Ozdil et al (2009) reported a negative correlation between HBV DNA and HBsAg in non-cirrhotic chronic HBV-infected patients, whereas Kuhns et al (2004) found no correlation between HBsAg and HBV DNA in 200 blood samples. This could be attributed to various factors: 1) differences in the sensitivity of the HBV DNA detection protocol; most previous studies set a lower limit of detection as 103 copies/mL (not 1.16 x 10 2 copies/mL); 2) antiviral treatment (that some of the patients were subjected to) can induce mutations in the HBsAg sequence; viral variants appear as a result of endogenous (host immunity) and/or exogenous (immune-prophylaxis and antiviral therapy) factors (Locarnini and Zoulim, 2010); and 3) the high spontaneous error rate in the reverse transcriptase induces mutations in the virus, such as the preS/S variants (Pollicino et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Ozaras et al (2008) suggested that the HBsAg level was correlated with HBV DNA, and that it could replace HBV DNA to monitor the efficacy of pegylated interferon in the presence or absence of lamivudine marker. On the other hand, Ozdil et al (2009) reported a negative correlation between HBV DNA and HBsAg in non-cirrhotic chronic HBV-infected patients, whereas Kuhns et al (2004) found no correlation between HBsAg and HBV DNA in 200 blood samples. This could be attributed to various factors: 1) differences in the sensitivity of the HBV DNA detection protocol; most previous studies set a lower limit of detection as 103 copies/mL (not 1.16 x 10 2 copies/mL); 2) antiviral treatment (that some of the patients were subjected to) can induce mutations in the HBsAg sequence; viral variants appear as a result of endogenous (host immunity) and/or exogenous (immune-prophylaxis and antiviral therapy) factors (Locarnini and Zoulim, 2010); and 3) the high spontaneous error rate in the reverse transcriptase induces mutations in the virus, such as the preS/S variants (Pollicino et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Although HBsAg assays are more sensitive in detecting HBV window-period infections, anti-HBc test can detect chronic carriers with low-level viremia without detectable HBsAg. The first few years of adding HBV NAT to routine screening of blood donations in the USA and Germany showed only a small yield [12,36], and other studies pointed out that 3% of HBV-infected donations would remain undetected even by ID NAT, thus reinforcing the need to maintain the HBsAg marker for routine blood screening [91]. More recently, PRISM CLIA claimed a 60% reduction of the HBV residual risk over MP NAT, from 1 : 385.555 to 1 : 610.488 [92].…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmaların birçoğunda HBsAg ve HBV DNA düzeyleri arasında pozitif korelasyon saptanmıştır (4,8,(15)(16)(17)(18). Bununla birlikte herhangi bir ilişkinin saptanmadığı (6,19,20) veya negatif ilişkinin saptandığı çalışmalar da (14) yayınlanmıştır. Biz çalışmamızda sadece HBsAg s/co değeri 400'e kadar olan hastalarda HBV DNA ile HBsAg arasında pozitif korelasyon saptarken tüm hastaları değerlendirdiğimizde negatif korelasyon olduğunu gördük.…”
Section: Discussionunclassified